Sports-related sudden cardiac death in Switzerland classified by static and dynamic components of exercise. (29th August 2020) - Gräni, Christoph; Chappex, Nina; Fracasso, Tony; Vital, Cristina; Kellerhals, Christoph; Schmied, Christian; Saguner, Ardan M; Trachsel, Lukas D; Eser, Prisca; Michaud, Katarzyna; Wilhelm, Matthias
Abstract: Background: Sports-related sudden cardiac deaths (SrSCDs) occur most frequently in highly dynamic and/or static sports. We aimed to assess the incidence and characteristics of SrSCDs in Switzerland and to compare SrSCD occurrence according to sports categories with the sports participation behaviour in the general population. Methods: Between 1999 and 2010, forensic reports of SrSCDs in young individuals (10–39 years of age) were retrospectively reviewed and categorised based on peak static (increasing from I to III) and dynamic sports components (increasing from A to C). Data were compared to the sports participation behaviour of the Swiss population. Results: Sixty-nine SrSCDs were identified. Forty-eight (69.6%) occurred during recreational sports (REC) and 21 (30.4%) during competitive sports (COMP). Incidences (per 100, 000 athlete person-years) for COMP and REC were 0.90 and 0.52, respectively ( p = 0.001). Most SrSCDs occurred in IC (23 cases, 33.3%), followed by IIC (13, 18.9%), IIIA and IIIC (11 each, 15.9%), IIIB (6, 8.7%), IIA (4, 5.8%) and IB sports categories (1, 1.5%). No SrSCDs were found in IA and IIB sports categories. Incidences between sports categories (IIIA 0.25, IB 0.25, IC 0.18, IIC 0.33 and IIIC 0.25) were not significantly different except to IIA (0.94, p < 0.001), due to the fact that few people were involved in this sports category. Coronary artery disease (CAD) was the most common underlying pathology of SrSCD. Conclusions: In this Swiss cohort, incidence of SrSCD was very low and similar in all sports categories classified by their static and dynamic components. However, the incidence was higher in COMP compared to REC, and CAD proved to be the most common underlying cause of SrSCD.